Pengelolaan Kas Masjid: Sebuah Upaya Menjaga Misi Dakwah - Nenie Sofiyawati (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
ABSTRACTA mosque’s cash management which is not based on managerial principles creates cash excess and shortage problems which affect to the cash availability to meet program needs. This condition results in the emergence of doubts from the congregation to the mosque management because the cash has not been allocated optimally for da’wa activities. This study uses a qualitative literature approach by using data sources such as books, journals, and others. Based on these results of empirical study on mosque cash management, this research yields a mosque cash management model based on mosque’s programs whose functions are as a place for improving piety, worshipping, praying, and purifying oneself. The ones including mosque cash management are as follows: designing organizational structure based on its function and position, arranging mosque’s work programs, projecting cash flow and time schedule for implementing mosque programs, and evaluating its implementations. Its implementations are in the forms of Mosque Revenue and Expenditure Budget which is used as an operational and controlling basis. Financial management based on planning can represent a trustworthy da’wah mission and reflect amar ma’ruf nahi munkar.